Core close-up images of IODP Hole 386-M0087B - Michael Strasser; Ken Ikehara; Jeremy D Everest; Lena Maeda; Katharina Hochmuth; Hannah Grant; Margaret S Stewart; Noriaki Sakurai; Takahiro Yokoyama; Rui Bao; Piero Bellanova; Morgane Brunet; et al. (PANGAEA, 2025)
Collection of split cores extquotesingle close-up images from the above given hole of International Ocean Discovery Program (IODP) Expedition 386 (Japan Trench Paleoseismology). The offshore phase of this expedition took place between 2021-04-13 and 2021-06-01 onboard Japanese R/V Kaimei from and to Yokosuka, Japan. Images were obtained during the onshore phase of the expedition, which took place between 2022-02-14 – 2022-03-15 onboard D/V Chikyu. Close-up photos were taken utilizing a standard photo camera by sedimentologists during visual core description. Decision on imaged intervals was subject to the core describers in charge. The standard IODP convention for labelling follows the syntax expedition number – hole – core plus core type ("H" [for hydraulic piston corer] indicates GPC cores, and "P" [for push corer] indicates trigger corer cores, see core summaries for further information) – section, top of interval in section [in cm] – bottom of interval in section [in cm], for instance "386-M0081A-1P-1,10-30" identifies a photo taken from the interval 10-30 cm within section 1 of core 1P from hole M0081A of expedition 386. For further methodological information see methods chapter in0.167emStrasser, M. et al., 2023 https://doi.org/10.14379/iodp.proc.386.102.2023